Urgensi Peranan Polisi Udara Dalam Penegakan Hukum Illegal Fishing Di Laut Natuna Utara - Triyatno, Deny; Rahayu, Setyaning; Saputra, Helmi Rizkih (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
The enforcement of laws in Indonesian waters, particularly in the North Natuna Sea, represents a serious challenge related to the protection of fishery resources, state sovereignty, and national security. This article aims to analyze the legal position and role of the Air Police within the fisheries law enforcement system as regulated under Law Number 2 of 2002 concerning the Indonesian National Police. This study employs a normative legal research method using statutory, conceptual, and analytical approaches. The findings indicate that the Air Police possess a legitimate legal standing as an integral part of the National Police in conducting surveillance, early detection, and operational support for law enforcement against illegal fishing, especially in strategic and vulnerable maritime areas. Aerial patrols function as a force multiplier that enhances the effectiveness of maritime law enforcement, which is often constrained by the limited reach of sea patrols. The study concludes that strengthening the role of the Air Police through inter-agency coordination is essential for sustainable and effective suppression of illegal fishing.